IDENTIFIKASI AKTIVITAS PEREMPUAN PENJUAL IKAN DI PASAR PEUNAYONG BANDA ACEH - Ruaida, Ruaida (Universitas Muhammadiyah Aceh, 2010)
This research is studying the working hours of women who work as fish seller at fish market Peunayong Banda Aceh. The working hours included both productive activity and daily household work (reproductive). The study also investigated the problem of raising their income and their contribution to the economy of their family. Twenty five of them were interviewed and their daily activities were directly observed in their work station. The interviews were tape-recorded and analyzed as qualitative and quantitative data. It is found that they worked in average of 16,5 hours a day, which is 12 hours for productive activity (buying & selling fish) and 4,5 hours they spent for household work (reproductive activity). For widow women, their income could support 86,70% of the daily need (Rp82.800 per day) and they often were trapped in debt. The income of married women could support 70,81% of their family need, and their husbands only supported 29,19% of the needs. They also complained lack of capital, less strategic places to sell fish, low bargaining from buyer. They often feel pain in their hand and get sick due to their work condition. At home, they often lose temper if their family does not want to help them at home. Key words: women, activity, and income DAFTAR PUSTAKA Abdullah, Irwan. 1997. Sangkan Paran Gender. Yogyakarta: Pustaka Pelajar. Al Yasa’ Abubakar. 2004. Antara Setia dan Durhaka, Ulasan Tentang Hak dan Kewajiban Suami Isteri. Nanggroe Aceh Darussalam : Biro Pemberdayaan Perempuan Sekda NAD Gadis Arivia. 2003. Filsafat Berperspektif Feminis. Jakarta: Yayasan Jurnal Perempuan. Herien Puspitawati, dan Ma’mun Sarma. 2007. “Analisis Gender Terhadap Penggunaan Dana Subsidi Langsung Tunai (SLT)- BBM Pada Keluarga Miskin Di Kota dan Kabupaten Bogor – Jawa Barat”, dalam Jurnal Pemberdayaan Perempuan. 2007:2, halaman:10-25. Kementerian Pemberdayaan Perempuan. 2004. Gender Dalam Perspektif Agama Islam. Jakarta: KPP Kelompok Kerja Convention Watch Pusat Kajian Wanita dan Gender Universitas Indonesia. 2004. Hak Azasi Perempuan. Jakarta : Yayasan Obor Indonesia. Marwansyah, dan Mukarram, 2000. Manajemen Sumber Daya Manusia. Bandung: Pusat Penerbit Administrasi Niaga Politeknik Negeri Bandung, Indonesia. Program Studi Kajian Wanita. 1999. Metodologi Penelitian Berperspektif Perempuan Dalam Riset Sosial. Jakarta: Program Pascasarjana Universitas Indonesia. Ruaida. 2007. “ Profil Perempuan Pengrajin Batu Bata Di Kabupaten Aceh Besar (Kajian Tentang Permasalahan yang Dihadapi Kaum Perempuan dengan Peran Beban Ganda)”, dalam Potret Pengalaman Perempuan Di Aceh Pasca Tsunami. Darussalam Banda Aceh. Pusat Studi Gender Universitas Syiah Kuala. Tapi Omas Ihromi. 2000. “Budaya dan Struktur yang Patriarkal : Reproduksi dan Resistensi? Tinjauan Terhadap Beberapa Hasil Penelitian Perempuan Dalam Sejumlah Kebudayaan Etnik di Indonesia”, dalam Perempuan Indonesia Dalam Masyarakat yang Tengah Berubah. Jakarta: Program Studi Kajian Wanita, Program Pasca Sarjana Universitas Indonesia. Tri Marhaeni P. Astuti. 2000. ”Gerakan Tandingan Perempuan, Kasus Migrasi Perempuan Kelas Bawah di Grobongan, Jawa Tengah”, dalam Perempuan Indonesia Dalam Masyarakat yang Tengah Berubah. Jakarta: Program Studi Kajian Wanita, Program Pasca Sarjana Universitas Indonesia. Saptari, Ratna, dan brigitte Holzner. 1997. Perempuan Kerja dan Perubahan Sosial. Jakarta: Grafiti